PENGARUH EMPLOYEE COMMUNICATION DAN CAREER DEVELOPMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Nurul Hikmah; Herman Sjahruddin; Rusni Rusni (Jurnal Bina Bangsa Ekonomika, 2024)
Since the promulgation of the Law on State Civil Servants (ASN), the management of civil servants (PNS) and government employees with work agreements (PPPK) has increasingly emphasized their qualifications, abilities and performance. One way to apply these three principles is to implement talent management, resulting in high individual performance. This Study aims to test the effect of civil servants communication and career development towards civil servants organizational citizenship behavior at the PUPR Region VIII Makassar Competency Development Center. The sample in this study was 45 respondents. This research uses multiple linear regression analysis techniques with the help of the SPSS Ver program. 27.0. The research results show that civil servants communication displayed by civil servants is at a good level so it is proven to increase civil servants organizational citizenship behavior in a good direction so does the career development of those that increase can also improve civil servants organizational citizenship behavior